Author, Edit Thyself. - Schriefer, Natalie (ASEE Prism, 2023)
The article focuses on providing tips to academics for improving the quality and acceptance chances of their scholarly work during the publishing process. Topics discussed include the benefits of reading work aloud to catch errors, batching tasks like reviewing reference lists and in-text citations, and the importance of carefully formatting tables and figures according to publication guidelines.
Keywords: Editing; Oral reading; Punctuation; Tense (Grammar); dept.hhs